Investigation of the temporal variability of thunderstorms in central and western Europe and the relation to large-scale flow and teleconnection patterns - Piper, David A.; Kunz, Michael; Allen, John T.; Mohr, Susanna (Quarterly Journal of the Royal Meteorological Society, 2019)
The driving factors that influence the spatial and annual variability of thunderstorms across Europe are still poorly understood. Due to a lack of long-term, reliable and consistent information about the occurrence of convective storms, a weather type classification has been developed that estimates thunderstorm probability from a combination of appropriate meteorological quantities on the mesoscale. Based on this approach, the temporal and spatial variability of convection-favouring environments is investigated between 1958 and 2014 using a high-resolution reanalysis dataset. To identify potential drivers for convective days, typical upper-level flow patterns were deduced using a multivariate approach. Our results suggest a strong link between local-scale thunderstorm activity and large-scale flow and air mass properties, such as stability, moisture, or vertical lifting. For example, while all over central Europe the most prominent pattern is given by a southwesterly flow type over the respective area, distinct regional discrepancies regarding further favourable flow types are observed. The crucial role of large-scale flow is further studied by assessing the relation between Northern Hemisphere teleconnection patterns and widespread convective activity. It is found that positive phases of the East Atlantic or Scandinavian patterns go along with a significant enhancement of convection-favouring conditions in several European regions, which can be explained by anomalies in the large-scale temperature and flow fields. Sea-surface temperature over the Bay of Biscay likewise impacts the convective environment, with the largest positive effect over the western part of the study area.